On the Diamond Bessel Heat Kernel - Wanchak Satsanit (Journal of Applied Mathematics)
We study the heat equation in n dimensional by Diamond Bessel operator. We find the solution by method of convolution and Fourier transform in distribution theory and also obtain an interesting kernel related to the spectrum and the kernel which is called Bessel heat kernel.